Answer:
3rd choice
Step-by-step explanation:
(7y^6)(2y^-4)^2
= (7y^6)(4y^-8)
Calculate:
(7y^6) * (4y^-8)
28y^-2
Express with a positive exponent:
28 * 1/y^2
Answer:
a = 1
Step-by-step explanation:
1. distribute the -6 on the left into the parentheses. you should get -36a + 30.
2. on the side right of the =, distribute the -2 to get -16 + 10a.
now it should look like -36a + 30 = -16 + 10a.
3. move the terms over to isolate the a value. subtract 30 to the right side to get -46 (-36a=-46+10a)
4. move the 10a on the right to the left by subtracting it to the other side.
(-46a=-46)
5.divide by -46 to get a=1
Answer:
<u>Nvgjvfknh</u>
Step-by-step explanation:
1.3 I think cause that's a percentage